Interpersonal challenges in surgical care provision in rural Mexico: A qualitative study - Valeria Macias; Zulema Garcia; William Pavlis; Zachary Fowler; Tarsicio Uribe-Leitz; Hannah Gilbert; Lina Roa; Mary-Jo DelVecchio Good (Elsevier, 2022)
Summary: Background: Chiapas is among the states with the lowest access to health care in Mexico. A better understanding of the role of interpersonal relationships in referral systems could improve access to care in the region. The purpose of this study was to analyze the underlying barriers and facilitators to accessing surgical care at public hospitals run by the Ministry of Health in Chiapas. Methods: In this qualitative interview study, we performed semi-structured interviews with 19 surgical patients and 18 healthcare workers at three public hospitals in the Fraylesca Region of Chiapas to explore barriers and facilitators to successfully accessing surgical treatment. Transcripts were coded and analyzed using an inductive, thematic approach to data analysis. Findings: The five major themes identified as barriers to surgical care were dehumanization of patients, the toll of rehumanizing patients, animosity in the system, the refraction of violence onto patients, and poor resource coordination. Three themes identified as facilitators to receiving care were teamwork, social capital, and accompaniment. Interpretation: Health care workers described a culture of demoralization and mistrust within the health system worsened by a scarcity of resources. As a result, patient care is hampered by conflict, miscommunication, and feelings of dehumanization. Efforts to improve access to surgical care in the region should consider strategies to improve teamwork and expand patient accompaniment. Funding: Harvard University and the Abundance Fund provided funding for this project. Funding sources had no role in the writing of the manuscript or decision to submit it for publication.Resumen Antecedentes: Chiapas es uno de los estados en Mexico con el menor acceso a la atención médica, y a los servicios quirúrgicos. Una mejor comprensión del papel de las relaciones interpersonales en los sistemas de referencias podría mejorar el acceso a la atención medica en la región. El objetivo del estudio es analizar las barreras y facilitadores para acceder a la atención quirúrgica en los hospitales públicos pertenecientes a la Secretaria de Salud del estado de Chiapas. Método: En este estudio cualitativo, realizamos entrevistas semiestructuradas con 19 pacientes quirúrgicos y 18 trabajadores de la salud en tres hospitales públicos en la región de la Frailesca de Chiapas para explorar barreras y facilitadores para acceder al tratamiento quirúrgico. Las transcripciones se codificaron y analizaron utilizando un enfoque temático. Resultados: Las cinco barreras principales identificadas fueron la deshumanización de los pacientes, el costo a re humanizar pacientes, la animosidad en el sistema, la refracción de la violencia sobre los pacientes y la mala coordinación de recursos. Tres facilitadores para recibir cirugía fueron el trabajo en equipo, el capital social, y el acompañamiento. Interpretaciones: Los trabajadores de la salud describieron una cultura de desmoralización y desconfianza en el sistema de salud que se agrava con la escasez de recursos. Como resultado se obtiene, conflicto, falta de comunicación, y sentimientos de deshumanización que empeoran la atención al paciente. Recomendaciones para mejorar el acceso a los servicios quirúrgicos en la región incluyen estrategias para mejorar el trabajo en equipo y ampliar el acompañamiento de los pacientes. Financiamiento: La Universidad de Harvard y the Abundance Fund proporcionaron fondos para este proyecto. Las fuentes de financiamiento no influyen en la redacción ni en la publicación del manuscrito.